What God said (London, 2013)
Inspired by his nine-book Conversations with God series, many people have asked Neale Donald Walsch to find a way to deliver the most essential pieces of God's message in a more succinct way. The result is a concise text detailing and expanding just what we need to know about life and how to live it. Bringing his many conversations over the years into sharper focus than ever before, Walsch encourages readers to cast aside religious and cultural trappings, and to build on, broaden, and enrich our Ancient Story. But to move forward on this ever-expanding and encompassing spiritual voyage means not only understanding what Walsch considers the most important insights of his Conversations with God, but also applying them in the most practical of ways. And so Walsch has included solid suggestions on how to apply each of the 25 Core Messages in daily life. Should humanity begin carrying these messages forward, starting today, we can change the world.
Keywords: "Spiritual life, God, Private revelations"